Optimal design of reactant delivery system in microfluidic fuel cell with porous electrodes. (30th June 2022) - Li, Li; Xie, Yajun; Shan, Shuai; Ling, Lei; Bei, Shaoyi; Zheng, Keqing; Xu, Qiang
Summary: Reactant delivery systems with different shaped inlet reservoirs bring significant volume increase to microfluidic fuel cells (MFCs). In this work, a two‐dimensional model is constructed for the flow through type MFC with porous electrodes and systematic analyses are performed for the optimization of the reactant delivery system to reduce the volume cost and meanwhile enhance the cell performance. Corresponding results show that though reservoir is essential in the MFC system, a narrow channel with a width on the order of a few tenths of a millimeter is already enough for the reactant distribution and thus the inlet reservoir size can be greatly reduced (93.33% under the flow rate of 300 μL min −1 ) without sacrificing the cell performance. A high flexibility is allowed for the reactant inlet size of the reservoir in the cases with high flow rates while larger inlet size is preferred in the cases with low flow rates. Optimal inlet position locates in the section close to the current collectors in the ohmic‐loss dominated cases. Yet, it moves to the middle section of the system with the decrease of reactant concentration or flow rate as concentration loss is responsible for the major performance loss in these cases. The results could provide instructive guidance for the optimization of reactant delivery system in MFC with porous electrodes. Abstract : Parametric analyses are performed for the optimization of the reactant delivery system in MFC with porous electrodes to reduce the volume cost and improve the cell performance at the same time. Some general rules are set for the optimal designs of reactant delivery systems under various operating conditions, which could provide useful guidance for the future development of MFC.